Primary adrenal melanoma with extensive metastasis: a case report and literature review - Guo, Qi; Shi, Dai; Li, Guilai; Liu, Yue; Xu, Guoping (Frontiers in Oncology, 2025)
Primary adrenal melanoma is an exceedingly rare diagnosis. We present a case of primary left adrenal melanoma with rapid and extensive distant metastasis. The patient underwent a biopsy of the left adrenal tumor, and pathological analysis confirmed malignant melanoma. Immunohistochemical staining revealed positive cytoplasmic reactivity for Melan A, HMB45, and SOX-10. We also review relevant cases reported in the English literature and discuss the diagnostic criteria, differential diagnoses, and potential management strategies.